2022
DOI: 10.1371/journal.pone.0275380
|View full text |Cite
|
Sign up to set email alerts
|

A meta-epidemiological assessment of transparency indicators of infectious disease models

Abstract: Mathematical models have become very influential, especially during the COVID-19 pandemic. Data and code sharing are indispensable for reproducing them, protocol registration may be useful sometimes, and declarations of conflicts of interest (COIs) and of funding are quintessential for transparency. Here, we evaluated these features in publications of infectious disease-related models and assessed whether there were differences before and during the COVID-19 pandemic and for COVID-19 models versus models for o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…In this study we verified previous code transparency results [10, 11], finding that less than 20% of randomly selected infectious disease modelling studies provide working links to code. Notably, the top-cited set of studies released code far more frequently (48%); however this is may be a function of the journals in which these articles were published and the mandates which they impose.…”
Section: Discussionsupporting
confidence: 87%
“…In this study we verified previous code transparency results [10, 11], finding that less than 20% of randomly selected infectious disease modelling studies provide working links to code. Notably, the top-cited set of studies released code far more frequently (48%); however this is may be a function of the journals in which these articles were published and the mandates which they impose.…”
Section: Discussionsupporting
confidence: 87%
“…When compared to transparency indicators in infectious disease models, another medical field where in-depth assessments have been conducted in the past 14 , our sample showed lower rates of code sharing (3% versus 21.5%), but similar rates of data sharing. Another paper 15 assessed transparency of COVID-19-related research in dental journals.…”
Section: Discussionmentioning
confidence: 82%
“…In our sample, most papers provided the model description; however, the code used to implement the model and create the results was reported in less than 25% of the studies. In the previous review of COVID-19 computational modeling studies, researchers found that a similar 21.5% of publications reported the code (n = 288) (20). With increasingly complex computational methodologies in infectious disease modeling literature, withholding the exact data manipulation and analysis steps can impede the consistent regeneration of modeling results.…”
Section: Discussionmentioning
confidence: 92%
“…Our estimate was similar to the 60% (n = 29) of CDC-compiled COVID-19 modeling studies analyzed by Jalali et al and much higher than the 24.8% (n = 332) reviewed by Ioannidis et al that reported to share their data. However, Ioannidis et al, used a text mining algorithm which may not have picked up publications that shared their data (19,20). Many journals now require researchers to provide a data availability statement when submitting a publication but allow researchers to circumnavigate the provision by stating “the datasets and code are available from the corresponding author on reasonable request.” Some publishers require authors to make their publication data publicly available (21).…”
Section: Discussionmentioning
confidence: 99%